Pozyskiwanie informacji wtórnej o rynkach zagranicznych za pomocą badań witryn internetowych wydziałów ekonomiczno-handlowych ambasad Rzeczypospolitej Polskiej - Filas, Marek (Gathering Secondary Information about Foreign Markets with the Use of Research of Economic and Commercial Sections of Polish Embassies Websites, 2006)
The paper describes the way of gathering secondary information about foreign markets which is researching websites of economic and commercial sections of Polish embassies. The paper presents the advantage of these websites over the others, characterizes them paying attention to the information they contain and describes website addresses of economic and commercial section of Polish embassies in Europe.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 646-652